Prevalência do aleitamento materno exclusivo e sua associação com trabalho materno em países da América Latina - Santos, Marília Neves (2020)
Introduction: Policies that guarantee women a break from work for at least six months after delivery increase the probability of exclusive breastfeeding for the same period. For women who work outside home, the return to work represents a determining moment that can directly interfere with the exclusivity and continuity or not breastfeeding. Most countries in Latin America developed their maternity protection laws between 1940 and 1970, but they still need improvement. Objective: To analyze the prevalence of EBF and the association with maternal work in Latin America. Methods: Cross-sectional study, conducted with data from the Demography and Health Surveys carried out in Bolivia(2008), Brazil(2006), Colombia(2010), Guatemala(2015), Haiti(2017), Honduras(2011), Peru(2011) and Dominican Republic(2007). The sample consisted of live children under six months of age and their mothers. The outcome was the EBF situation(yes/no) and the main predictor variables were maternal work(yes/no), type of occupation (managerial; administrative; sales; agriculture; domestic; manual labor) and employment modality (formal/informal). Information on maternity leave was collected form country-specific documents and labor laws. The association between EBF and predictor variables was performed using Poisson regression, adjusted for maternal education, presence of partner, place of residence, maternal age, type of delivery, primiparity, wealth índex and breastfeeding in the first hour. Results: The prevalence of EBF was 58.0% in Bolivia, 41.1% in Brazil, 39.2% in Colombia, 50.8% in Guatemala, 39.7% in Haiti, 31.1% in Honduras, 68.1% in Peru and 7.6% in the Dominican Republic. The percentage of women who declared to work was 46.1% in Bolivia, 24.1% in Brazil, 28% in Colombia, 19.5% in Guatemala, 21.3% in Haiti, 23.3% in Honduras, 35.4% in Peru and 19.1% in the Domican Republic. Among the women who declared to work, the percentage of women in formal work was 43.9% in Bolivia, 87.4% in Colombia, 60.5% in Guatemala, 83.3% in Haiti, 72.2% in Honduras, 56.8% in Peru and 64.7% in the Dominican Republic. The most prevalent type of occupation was in the sales área, except in Bolivia, where the majority work in agriculture. Maternity leave ranged from 12 to 18 weeks in these countries. Maternal work was negatively associated with EBF in Guatemala (PR:0.80; CI95%:0.65;0.98), Haiti (PR:0.68; CI95%:0.51;0.90) and Honduras (PR:0.65; CI95%: 0.46;0.91). These three countries had the shortest maternity leave, while in Guatemala and Honduras, 2/3 of the subsidy was the responsability of social security and 1/3, of the employer. In Haiti, 100% of the subsidy was the responsability of the employer. Informal work was negatively associated with EBF in Honduras (0.74; CI: 0.55; 0.99). As for the type of employment, domestic work was negatively associated with EBF in the Dominican Republic (0.28; CI: 0.08; 0.93). Conclusion: The prevalence of EBF was lower in women who were working in three countries in Latin America, which also had shorter duration of maternity leave. Maternal work in the informal economy needs to be further investigated since this type of employment was negatively associated with EBF in one of the countries analyzed.